Analisis Dan Perancangan Manajemen Bandwidth Menggunakan Metode HTB Dengan Mikrotik Pada Jaringan SMA Negeri 4 Palembang - Hafizena, M. Fahri; Putri, Dhanny Permatasari (Universitas Batanghari Jambi, 2023)
The quality of the internet is not good when school residents access the internet, poor Quality of service (QoS) results have not been maximized when compared to TIPHON standardization. the author wants to implement queue bandwidth management through the Hierarchical Token Bucket (HTB) method. Based on the formulation of the problem above, the objectives to be achieved in this study are to implement bandwidth management using the HTB method on the Mikrotik Routerboard type RB951Ui-2ND so that the quality of QoS services at SMA Negeri 4 Palembang is better and optimal. The results of this study are expected to help administrators or Heads of Computer Lab networks at SMA Negeri 4 Palembang to implement bandwidth management using the HTB method. the hierarchical token bucket HTP method is very effective for managing network tarfik so that bandwidth is better managed.